2019
DOI: 10.3390/ijms20194791
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Cell Cycle-Related Genes in Human Fibroblasts Exposed Simultaneously to Radiation and Simulated Microgravity

Abstract: Multiple unique environmental factors such as space radiation and microgravity (μG) pose a serious threat to human gene stability during space travel. Recently, we reported that simultaneous exposure of human fibroblasts to simulated μG and radiation results in more chromosomal aberrations than in cells exposed to radiation alone. However, the mechanisms behind this remain unknown. The purpose of this study was thus to obtain comprehensive data on gene expression using a three-dimensional clinostat synchronize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 75 publications
3
24
0
1
Order By: Relevance
“…This increase in complex DNA damage in comparison with X-ray exposure has been previously observed [97] and could involve the triggering of chromosomal translocations [98]. Recent reports show downregulation of cell cycle suppressing genes (ABL1 and CDKN1A) and upregulation of cell cycle promoting genes (CCNB1, CCND1, KPNA2, MCM4, MKI67 and STMN1) in cells exposed to HZE particles under microgravity [99]. HZE particles themselves induce complex DNA damage and arrest DNA repair process, and also failure to arrest at the G1/S, G2 checkpoints under microgravity; the combination of these responses will lead to genomic instability, including chromosome aberrations, and eventually lead to malignant transformation of those cells.…”
Section: Discussionsupporting
confidence: 66%
“…This increase in complex DNA damage in comparison with X-ray exposure has been previously observed [97] and could involve the triggering of chromosomal translocations [98]. Recent reports show downregulation of cell cycle suppressing genes (ABL1 and CDKN1A) and upregulation of cell cycle promoting genes (CCNB1, CCND1, KPNA2, MCM4, MKI67 and STMN1) in cells exposed to HZE particles under microgravity [99]. HZE particles themselves induce complex DNA damage and arrest DNA repair process, and also failure to arrest at the G1/S, G2 checkpoints under microgravity; the combination of these responses will lead to genomic instability, including chromosome aberrations, and eventually lead to malignant transformation of those cells.…”
Section: Discussionsupporting
confidence: 66%
“…We found that the expression of cell cycle-suppressing genes decreased, and that of cell cycle-promoting genes increased after C-ion irradiation under µG compared with irradiation [19]. The cell cycle may pass through the checkpoints with DNA damage due to the combined effects of C-ion and µG, suggesting that increased genomic instability might occur in space [19]. Indeed, we also found an increased frequency of chromosome aberrations (CA) in cells exposed to both radiation and µG, compared to those treated by radiation only [20].…”
Section: Introductionmentioning
confidence: 80%
“…Using these experimental set-ups, we have earlier studied the combined effects of radiation and µG on human fibroblasts, which are adherent cells. We found that the expression of cell cycle-suppressing genes decreased, and that of cell cycle-promoting genes increased after C-ion irradiation under µG compared with irradiation [19]. The cell cycle may pass through the checkpoints with DNA damage due to the combined effects of C-ion and µG, suggesting that increased genomic instability might occur in space [19].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations